Intein Inhibitors as Novel Antimicrobials: Protein Splicing in Human Pathogens, Screening Methods, and Off-Target Considerations - Wall, Diana A.; Tarrant, Seanan P.; Wang, Chunyu; Mills, Kenneth V.; Lennon, Christopher W. (Frontiers in Molecular Biosciences, 2021)
Protein splicing is a post-translational process by which an intervening polypeptide, or intein, catalyzes its own removal from the flanking polypeptides, or exteins, concomitant with extein ligation. Although inteins are highly abundant in the microbial world, including within several human pathogens, they are absent in the genomes of metazoans. As protein splicing is required to permit function of essential proteins within pathogens, inteins represent attractive antimicrobial targets. Here we review key proteins interrupted by inteins in pathogenic mycobacteria and fungi, exciting discoveries that provide proof of concept that intein activity can be inhibited and that this inhibition has an effect on the host organism’s fitness, and bioanalytical methods that have been used to screen for intein activity. We also consider potential off-target inhibition of hedgehog signaling, given the similarity in structure and function of inteins and hedgehog autoprocessing domains.